New species of Tauala Wanless, 1988 from Australia (Araneae: Salticidae: Astioida: Astiae), with a redefinition of the genus - Żabka, Marek; Patoleta, Barbara M. (Zootaxa, 2015)
Five species of the genus Tauala Wanless, 1988, namely T. zborowskii sp. nov. (f), T. ottoi sp. nov. (f), T. palumaensis sp. nov. (m), T. bilobatus sp. nov. (m) and T. setosus sp. nov. (m), are diagnosed, described and illustrated. Additional colour plates with the females of T. lepidus Wanless, 1988 and T. athertonensis Gardzińska, 1996 and the male of T. splendidus Wanless, 1988 are provided, as well as distributional maps for these three species. Tauala elongata Peng & Li, 2002 is considered a non-congener. A revised definition of the genus is proposed and its distribution and relationships are discussed.